2019
DOI: 10.1098/rsos.190854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of baobab (Adansonia digitataL.) in southeastern Kenya

Abstract: Baobab ( Adansonia digitata L.) is an iconic tree of African savannahs. Its multipurpose character and nutritional composition of fruits and leaves offer high economic and social potential for local communities. There is an urgent need to characterize the genetic diversity of the Kenyan baobab populations in order to facilitate further conservation and domestication programmes. This study aims at documenting the genetic diversity and structure of baobab populations in southeastern Kenya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The other three studies used microsatellites to assess genetic diversity, the first in seven coastal and inland Kenyan populations [68], the second in populations of the Nuba Mountains of Sudan [69] and the third in Malawi [67]. All these genetic studies also found high morphological diversity in fruits and/or leaves.…”
Section: Genetic Variationmentioning
confidence: 99%
“…The other three studies used microsatellites to assess genetic diversity, the first in seven coastal and inland Kenyan populations [68], the second in populations of the Nuba Mountains of Sudan [69] and the third in Malawi [67]. All these genetic studies also found high morphological diversity in fruits and/or leaves.…”
Section: Genetic Variationmentioning
confidence: 99%
“…It is a very important tree with multiple benefits and is a source of traditional food in Saharan countries [ 433 ]. Additionally, it is also a source of medicine, fiber and income for rural communities [ 434 , 435 ]. Almost all its parts can be consumed and it contains high vitamin C content as compared to oranges [ 434 ].…”
Section: Examples Of Application Of Multi-omics Tools To Traditional Food Plantsmentioning
confidence: 99%
“…Almost all its parts can be consumed and it contains high vitamin C content as compared to oranges [ 434 ]. Using microsatellite loci, Chládová et al [ 435 ] suggested huge genetic diversity among its populations. However, further research is needed to understand the genetic basis of the higher accumulation of vitamin C and other important compounds that make it a wonder tree.…”
Section: Examples Of Application Of Multi-omics Tools To Traditional Food Plantsmentioning
confidence: 99%
“…It is a very important tree with multiple benefits including a source of traditional food in the Saharan countries [206]. Additionally, it is also a source of medicine, fibre and incomes for the rural communities [207,208]. Almost all its parts can be consumed and it contains high vitamin C content as compared to oranges [207].…”
Section: Transcriptional Basis Of Lipid Biosynthesis In Chia a Wonder Seed For The 21st Centurymentioning
confidence: 99%
“…Almost all its parts can be consumed and it contains high vitamin C content as compared to oranges [207]. Using microsatellite loci, Chládová et al [208] have suggested a huge genetic diversity among its populations. However, further research is needed to understand the genetic basis of the higher accumulation of the vitamin C and other important compounds that make it a wonder tree.…”
Section: Transcriptional Basis Of Lipid Biosynthesis In Chia a Wonder Seed For The 21st Centurymentioning
confidence: 99%